Iman yang Bertumbuh dalam Tindakan: Implikasi Konsep Tabula Rasa dan Pendidikan Ekologi bagi Anak Sekolah Minggu Huria Kristen Batak Protestan - Manalu, Musdodi (KENOSIS: Jurnal Kajian Teologi, 2024)
This article explores the integration between John Locke's concept of tabula rasa and ecological education for Sunday School children in the Huria Kristen Batak Protestan (HKBP) Church. The research aims to investigate how Locke's philosophical concept of the mind as an empty "tabula rasa," which is filled through experience and learning, can be applied in the context of children's faith growth. The main focus is on ecological education, where the article explains how a holistic approach to faith growth involves children's understanding of their relationship with nature and the surrounding community. This concept is explicitly applied in HKBP Sunday School, highlighting the church's efforts in delivering religious teachings and facilitating hands-on experiences that can shape children's faith. Combining Locke's and Susan Power Bratton's thoughts on ecological education, this article offers insights into how faith can develop through action and tangible experiences, creating a solid foundation for children's spiritual growth in an ecologically conscious ecclesial environment and active learning. The research method used was a literature review that included books, journal articles, and news related to ecological education. The research used thematic analysis to identify and report patterns or themes in the data obtained from literature sources. The main contribution of this research is the integration of ecological principles in the context of children's worship as embodied in the HKBP Sunday School Handbook, updated annually.